In vitro regeneration of Arachis villosulicarpa hoehne from cotyledon segments, leaves and cell suspension - Mansur, Elisabeth; Lacorte, Cristiano; Rabelo, Aurora C. G.; Cordeiro, Antônio R. (Pesquisa Agropecuaria Brasileira, 1993)
In vitro regeneration from immature leaves and cotyledon segments of A. villosulicarpa Hoehne was obtained on Murashige & Skoog medium (1962) plus 1.0 mg/l 1-naphthalene acetic acid (NAA) and 1.0 mg/l 6-benzylaminopurine (BAP). Cotyledon segments showed higher morphogenetic potential than immature leaves. Morphogenic calli could also be obtained from leaves of regenerated plants propagated in vitro. Cell suspension cultures were established from friable calli originated from leaf and cotyledon explants cultured on MS medium supplemented with 0.2 mg/l picloram and 1.0 mg/l BAR. Calli from liquid culture developed shoots on regeneration medium. Root differentiation of plantlets was achieved on liquid MS medium.